98 Saint Catherine's hospice mortality review; service development and audit. (14th March 2023) - Adams, Charlotte
Abstract : Background: Following on from the National Guidance on Learning from Deaths (NHS England 2017), and in preparation for the new medical examiner system, we have formalised our mortality review processes. We developed a death analysis template to be completed after each patient death alongside a monthly mortality review meeting (MRM) with multi-disciplinary team (MDT) and hospital input. The template is completed by a patient's key worker, reviewed in the weekly MDT meeting and those triggering certain criteria have an in-depth discussion at the monthly MRM. A random case is also always included. Methods: We performed a quarterly audit of numbers of patients with a completed death analysis template while the system was being embedded. We then performed a more in-depth audit of all patients discussed over the past year in the new MRM. This included both quantitative elements such as age and diagnosis and then also qualitative elements such as themes arising and actioned outcomes. Results: 93% of all patient deaths had a template completed and subsequent discussion at the relevant MDT meeting. 16% of those patients went on to be discussed in a MRM. Time of death to discussion at MRM was a mean of 39 days. Themes for improvement included missed opportunities for advance care planning, earlier referral to palliative care services and resources to improve overall patient wellbeing in the in-patient unit. Examples of actions taken forward include hospital-hospice handover work, positive feedback letters sent to carers and sourcing of an in-patient electronic audiobook library. Conclusions: We have put in place a robust structure to promote learning from deaths. Our work with the medical examiner service is about to begin to add breadth to this and will also importantly include family feedback. With ongoing refinement this new governance structure should continue to impact positively on patient care.